(untitled) (Health Renaissance, 2011)
Setting: College of Dental Surgery, B P Koirala Institute of Health Sciences, Sunsari, Nepal. Aims: To evaluate the pattern and distribution of malocclusions in patients seeking for orthodontic treatment from Sunsari district of Nepal. Material and Methods: Total of 350 patients who were permanent inhabitants of Sunsari district of age range 8-36 years were included in the study. A standard format was prepared to record the data. Descriptive statistics for mean, standard deviation and frequencies were calculated. Ages and Class I, II and III malocclusions were cross tabulated to check for any relationship using ANOVA. Intra investigator error was calculated using kappa statistics. Results: The prevalence of Class I, II and III malocclusions were 62.28 %, 29.4%.and 8.2% respectively. Out of 350 cases studied for various occlusal traits the nature of distribution of various occlusal findings were: absent teeth-12.6%, supernumerary teeth-2.9% ectopic eruption-7.1%, midline diastema-16%, incisor crowding-52.9%, spacing-30%, malformations-3.1%, increased overjet (>4mm)- 42.3%, anterior open bite . 5.1% and deep bite (>4mm )- 40 % and cleft lip and palate was 0.28%. Most prevalent age group seeking orthodontic treatment was 12-24 years with females to male ratio of 2.3:1 Comparison of mean ages with different malocclusion groups using ANOVA was statistically not significant. Conclusion: Class I malocclusion was the most prevalent followed by Class II malocclusion and the Class III malocclusion showed least prevalence. There were diverse occlusal traits. Keywords: Malocclusion; Angle’s Classification; Sunsari; BPKIHS